'It seems like common sense now': experiences of allied health clinicians participating in a knowledge translation telementoring program. Issue 3 (29th September 2022) - Wilkinson, Shelley A.; Hickman, Ingrid; Cameron, Ashley; Young, Adrienne; Olenski, Samantha; BPhty, Prue McRae; O'Brien, Maxine
ABSTRACT: Introduction and aims: Clinicians understanding and applying the skills of knowledge translation is essential for the delivery of high value, effective health care. However, many clinicians lack confidence and capacity to undertake knowledge translation. Our team recently piloted a group telementoring knowledge translation support service (KTSS) with allied health professionals (AHPs) undertaking knowledge translation in their practice. This article aims to investigate barriers and enablers to participants' participation and identify evidence-based strategies to improve future delivery of the initiative. Methods: The evaluation utilized semistructured interviews with participants who completed the first KTSS. Interview transcripts were analysed to identify key themes and subthemes. Subthemes were also mapped to an implementation science framework and model (theoretical domains framework and behaviour change wheel) to guide evidence-based identification of effective strategies to address, overcome, or enhance issues raised. Results: Six of the nine participants invited were interviewed. Five barriers and six enablers of KTSS participation, and five improvement ideas for a future KTSS program, were suggested. Barriers included knowledge gaps, competing time demands, and organizational expectations. Enablers included organizational support, motivation and preparation, and local champions. Additional strategies included additional preparation, an initial rapport building session, and strategies to meet the emotional needs of the participants. These were reinforced by the framework mapping results, with the further addition of a peer modelling strategy. Conclusion: Through a qualitative methodology we have examined and identified the experiences of AHPs who have participated in a knowledge translation telementoring program with clear strategies to enhance further programs offered.